Dividend Policy, Investment Decisions, and Firm SIze: Do They Matter for Firm Value? Evidence from IDX High Dividend 20 - Moch. Qolba Faradea; Abid Djazuli; Fadhil Yamaly (Universitas Muhammadiyah Palembang, 2025)
Purpose - This study aims to determine the influence of Dividend Policy, Investment Decisions, and Firm Size on Firm Value in High Dividend 20 Index Companies on the Indonesia Stock Exchange. Design/methodology - The research method used is associative. The sample consists of 18 High Dividend 20 Index companies listed in 2024 for the period 2019–2023. The data used is secondary data obtained from the official website (www.idx.co.id) or the respective company websites. The data collection method employed in this study is document analysis. The data analysis technique used is quantitative analysis to examine Dividend Policy, Investment Decisions, and Firm Size. Statistical analysis is then conducted using Financial Analysis, Classical Assumption Tests, Multiple Linear Regression, and Hypothesis Testing, which includes the F-test and t-test. Findings - The results of this study indicate that Dividend Policy, Investment Decisions, and Firm Size collectively have a significant influence on Firm Value. Additionally, Dividend Policy and Investment Decisions each have a significant partial influence on Firm Value. However, Firm Size does not have a significant influence on Firm Value in High Dividend 20 Index Companies listed on the Indonesia Stock Exchange.